Virolinguistics: Introduction to the Study of the Coronavirus Language - Béla Istók; Gábor Lőrincz (Acta Universitatis Sapientiae: Philologica)
This paper undertakes the introduction to virolinguistics, a new linguistic discipline that investigates the virus language (virolect) based on the Hungarian linguistic material drawn from the scientific literature and our own collection. The goal of this work is to evaluate the effect of the pandemic on certain aspects of the Hungarian language: genres, vocabulary, communication, the linguistic landscape, and social media. The linguistic materials of these various areas play an important role in our society: they have a warning, entertaining, or stress-relieving function. Due to the restrictions, most studies have moved to the Internet. The methodological paradox of virolinguistics can be identified in the fact that it disregards certain scientific standards in order to assist linguists in collecting their valuable linguistic and visual materials.